Dit siin .24. tekene der doot die Ypocras met hem dede grauen e la ricezione della Capsula eburnea in nederlandese medio - Valeria Di Clemente (Filologia Germanica)
The Late Antique pseudo-hippocratic prognostic text known as Capsula Eburnea Hippocratis enjoyed wide diffusion in the Middle Ages and was repeatedly translated into many European vernaculars. The Middle Dutch version titled Dit siin .24. tekene der doot die Ypocras met hem dede grauen dates back to the middle of the fourteenth century and is found in a manuscript containing heterogeneous medical and naturalistic works and excerpts. A new edition of the text is presented here, along with an Italian translation, an ecdotic and linguistic commentary and a comparison of the Middle Dutch version with its Latin source.